Process Development for Wet‐Chemical Surface Functionalization of Gallium Arsenide Based Nanowires. Issue 4 (14th March 2019) - Speich, Claudia; Dissinger, Frank; Liborius, Lisa; Hagemann, Ulrich; Waldvogel, Siegfried R.; Tegude, Franz‐Josef; Prost, Werner
Abstract : The chemisorption of various functionalizing agents on (100) and (111)B gallium arsenide and (100) indium phosphide substrates is studied to elaborate a wet‐chemical surface coating protocol for gallium arsenide based nanowires. Application of (non‐)fluorinated alkanethiols under different parameters shows great success resulting in a decreased polarity of the surface (confirmed by a significant increase of the water contact angle) and no occurrence of etching effects. The successful functionalization is determined by X‐ray photoelectron spectroscopy measurements. After optimization of concentration, additives and solvents, the process parameters are transferred to both, p‐ and n‐doped GaAs‐based nanowire structures. The influence of surface functionalization on the electrical behavior of the nanowires is determined by current–voltage characteristics. Based on the experimental data, a bonding mechanism for the alkanethiol onto the semiconductor material is proposed and a model for describing surface depletion before and after functionalization is developed. Abstract : The chemisorption of fluorinated alkanethiols agents on gallium arsenide substrates is studied to elaborate a wet‐chemical surface coating for gallium arsenide based nanowires. The successful functionalization is determined by contact angle goniometry, X‐ray photoelectron spectroscopy, and current–voltage measurements. A bonding mechanism for alkanethiol onto the semiconductor material is proposed describing surface depletion before and after functionalization.